Advanced technologies, systems, and applications III : proceedings of the International Symposium on Innovative and Interdisciplinary Applications of Advanced Technologies (IAT).: proceedings of the International Symposium on Innovative and Interdisciplinary Applications of Advanced Technologies (IAT). Volume 2 ([2019]) - Unknown
No abstract available